Remarkable variation of ribosomal DNA organization and copy number in gnetophytes, a distinct lineage of gymnosperms - Wang, Wencai (Ann Bot, 2019)
INTRODUCTION: Gnetophytes, comprising the genera Ephedra, Gnetum and Welwitschia, are an understudied, enigmatic lineage of gymnosperms with a controversial phylogenetic relationship to other seed plants. Here we examined the organization of ribosomal DNA (rDNA) across representative species. METHODS: We applied high-throughput sequencing approaches to isolate and reconstruct rDNA units and to determine their intragenomic homogeneity. In addition, fluorescent in situ hybridization and Southern blot hybridization techniques were used to reveal the chromosome and genomic organization of rDNA. KEY RESULTS: The 5S and 35S rRNA genes were separate (S-type) in Gnetum montanum, Gnetum gnemon and Welwitschia mirabilis and linked (L-type) in Ephedra altissima. There was considerable variability in 5S rDNA abundance, ranging from as few as ~4000 (W. mirabilis) to >100 000 (G. montanum) copies. A similar large variation was also observed in 5S rDNA locus numbers (two to 16 sites per diploid cell). 5S rRNA pseudogenes were interspersed between functional genes forming a single unit in E. altissima and G. montanum. Their copy number was comparable or even higher than that of functional 5S rRNA genes. In E. altissima internal transcribed spacers of 35S rDNA were long and intrinsically repetitive while in G. montanum and W. mirabilis they were short without the subrepeats. CONCLUSIONS: Gnetophytes are distinct from other gymnosperms and angiosperms as they display surprisingly large variability in rDNA organization and rDNA copy and locus numbers between genera, with no relationship between copy numbers and genome sizes apparent. Concerted evolution of 5S rDNA units seems to have led to the amplification of 5S pseudogenes in both G. montanum and E. altissima. Evolutionary patterns of rDNA show both gymnosperm and angiosperm features underlining the diversity of the group.